Prevalence of active and passive smoking during pregnancy: a cross-sectional study - Wallysson Costa Batista; Poliana Valdelice Cruz; Cristiane Baccin Bendo; Carolina Castro Martins (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2020)
Purpose: The aim of the present study was to evaluate the prevalence of active and passive smoking during pregnancy and its association with sociodemographic indicators, as well as perinatal and postnatal outcomes in newborns. Methods: This cross-sectional study was comprised of 431 pairs of mothers/ newborns. The study variables were: preterm birth, birth weight, oral mucosal lesions, sociodemographic indicators and smoking data. We collected data from medical records and through a self-administered questionnaire answered by mothers. A pediatric dentist examined the newborns for oral mucosal lesions. Bivariate and multivariate logistic regression models were used to evaluate the association between active and passive smoking and the other variables (α=5%). Results: The prevalence of active (9.5%) and passive smoking (4.2%) during pregnancy was low. Active smoking was statistically associated with low birth weight (OR: 2.4; 95%CI:1.1-5.3), lower schooling level (OR: 0.2; 95%CI:0.1-0.5) and mothers aged ≥36 years old (OR: 4.9; 95%CI:1.2-20.0). Passive smoking was not statistically associated with the other variables. There was no association between active or passive smoking during pregnancy and premature birth and oral lesions of the newborn. Conclusions: The prevalence of active and passive smoking were low. Active smoking was associated with low birth weight, maternal age and mother's schooling, suggesting a social influence of smoking behavior among a population with a lower educational level. There was no association between active and passive smoking and prematurity and oral lesions of the newborn.